Q: What is the answer x2 equals 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x = x2 + 4x - 3 x2 + 2x - 3 = 0 (x - 1)(x - 2) = 0

3

x2+3=124 x2=121 x= square root(121) x=11

-x2 = x - 6 x2 + x - 6 = 0 (x - 2)(x + 3) = 0 x ∈ {-3, 2}

-4

Related questions

If: x2 = 3 Then: x = square root of 3

2x = x2 + 4x - 3 x2 + 2x - 3 = 0 (x - 1)(x - 2) = 0

No translation will invert a quadratic graph.

3

x2+3=124 x2=121 x= square root(121) x=11

-x2 = x - 6 x2 + x - 6 = 0 (x - 2)(x + 3) = 0 x ∈ {-3, 2}

x2 + 2x - 15 = (x - 3)(x + 5)

-4

In general, no.

y = 4x-3

x2 + 6x + 12 = 0 x2 + 6x + 9 = -3 (x + 3)2 = -3 x + 3 = ± √-3 x = -3 ± i√3

x2 + x2 = 2x2